Occurrence of sulfonated steroids and ovarian expression of steroid sulfatase and SULT1E1 in cyclic cows. Issue 179 (May 2018) - Blaschka, Carina; Schuler, Gerhard; Sánchez-Guijo, Alberto; Zimmer, Bettina; Feller, Sabine; Kotarski, Franziska; Wudy, Stefan A.; Wrenzycki, Christine
Highlights: Expression patterns of STS and SULT1E1 in bovine ovary. Sulfonated steroids concentrations below the limit of quantification in blood. High concentrations of cholesterol sulfate in follicular fluid. Other sulfonated steroids virtually undetectable in follicular fluid. No considerable sulfonation of C21-, C19- and C18-steroids in bovine ovary. Abstract: Historically sulfonated steroids were primarily considered as inactive metabolites destined for elimination. However, more recently they have been increasingly recognized as precursors for the production of bioactive steroids in target tissues and as functional molecules without preceding hydrolysis. In order to comprehensively characterize their occurrence in cyclic cows and their formation and hydrolysis in bovine ovarian steroidogenesis, ovaries from cyclic cows were screened for the expression of oestrogen sulfotransferase (SULTE1) and steroid sulfatase (STS) by Western blot and immunohistochemistry. Moreover, a broad spectrum of 13 sulfonated steroids was measured applying liquid chromatography-tandem mass spectrometry (LC–MS/MS) in blood samples collected from three cycling heifers during defined stages of the ovarian cycle and in fluid obtained from ovarian follicles of different size. SULT1E1 was undetectable in ovarian tissues. For STS only a weak immunostaining was found predominantly in granulosa cells of larger follicles. However, no specific band occurred in Western blot. In blood, concentrations of all sulfonated steroids investigated were below the limit of quantification (LOQ). In follicular fluid, only cholesterol sulfate was measured in considerable concentrations (328.3 ± 63.8 ng/ml). However, the role of cholesterol sulfate in bovine follicular steroidogenesis remains unclear as concentrations were obviously unrelated to follicular size. The remaining sulfonated steroids investigated were undetectable or only slightly exceeded LOQ in a minor proportion of samples. The results are clearly contrary to a role of sulfonated steroids as important precursors, intermediates or products of bovine ovarian steroidogenesis.